A high integration electrowetting displays system based on AC driving model - Li, Shixiao; Xu, Yijian; Zhan, Zhiyu; Liu, Linwei; Bai, Pengfei (Frontiers in Physics, 2022)
As a representative of new reflective display technology, the electrowetting display (EWD) has been widely accepted for its good advantages in power consumption control and display contrast. Because of charge trapping and contact angle hysteresis, static images cannot be maintained and afterimage phenomenon occurs, respectively. These problems seriously affect the EWDs display effect. In order to improve the video display effect of EWDs, an alternating current (AC) driving model was proposed in this paper. Firstly, a high integration EWDs system was built with Xilinx field programmable gate array (FPGA). Secondly, an asymmetric intermediate frequency (IF) AC driving model was proposed to eliminate the afterimage of the video. Finally, the optimized driving method was applied to the EWDs system to achieve a high-smooth display output. The experimental results showed that the problem of afterimage and the problem of static image preserving display were effectively solved. Compared with the traditional AC driving waveform, the maximum reflected luminance of the proposed method was increased by 14%, and the refresh rate of EWDs could reach 60 Hz.